2004
DOI: 10.1016/j.pain.2004.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin for the treatment of painful diabetic peripheral neuropathy: a double-blind, placebo-controlled trial

Abstract: A randomized, double-blind, placebo-controlled, parallel-group, multicenter, 8-week trial (with subsequent open-label phase) evaluated the effectiveness of pregabalin in alleviating pain associated with diabetic peripheral neuropathy (DPN). For enrollment, patients must have had at baseline: 1- to 5-year history of DPN pain; pain score > or =40 mm (Short-Form McGill Pain Questionnaire [SF-MPQ] visual analogue scale); average daily pain score of > or =4 (11-point numerical pain rating scale [0 = no pain, 10 = w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
400
8
14

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 627 publications
(456 citation statements)
references
References 32 publications
34
400
8
14
Order By: Relevance
“…Beginning at week 1, the highest three mirogabalin dosing groups (15,20, and 30 mg/day) had significantly greater mean reductions from baseline to week 5 in ADPS compared with placebo, and one dosing group (30 mg/day) met the criteria for minimally clinically meaningful effect (i.e., a decrease $1.0 point versus placebo). These data are compelling given the study population had DPNP for a mean of 5.8 years, which is longer than those who participated in pregabalin trials, where subjects were excluded if the duration of DPNP was .5 years (20,(23)(24)(25). Analysis of responders, defined as subjects who attained $30 or $50% reduction from baseline in ADPS, were generally supportive of a mirogabalin treatment effect compared with placebo, as improvements relative to placebo were statistically significant at 15-, 20-, and 30-mg/day dose levels using one or both responder definitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beginning at week 1, the highest three mirogabalin dosing groups (15,20, and 30 mg/day) had significantly greater mean reductions from baseline to week 5 in ADPS compared with placebo, and one dosing group (30 mg/day) met the criteria for minimally clinically meaningful effect (i.e., a decrease $1.0 point versus placebo). These data are compelling given the study population had DPNP for a mean of 5.8 years, which is longer than those who participated in pregabalin trials, where subjects were excluded if the duration of DPNP was .5 years (20,(23)(24)(25). Analysis of responders, defined as subjects who attained $30 or $50% reduction from baseline in ADPS, were generally supportive of a mirogabalin treatment effect compared with placebo, as improvements relative to placebo were statistically significant at 15-, 20-, and 30-mg/day dose levels using one or both responder definitions.…”
Section: Discussionmentioning
confidence: 99%
“…1. No titration was used in mirogabalin 5-, 10-, 15-, and 20-mg/day dosing arms to assess quicker pain relief (20).…”
Section: Methodsmentioning
confidence: 99%
“…In a separate randomized controlled PHN trial, Sabatowski et al 84 found that, at a dose of 300 mg/day compared with placebo, patients receiving pregabalin not only had significant pain reduction but also enjoyed improvement in sleep and mood. In another eight-week randomized placebo-controlled trial, Rosenstock et al 85 evaluated the potential efficacy of pregabalin in reducing pain associated with DPN. Use of pregabalin at a dose of 300 mg/day resulted in significant improvements in mean pain scores, the patient, and clinical global impression of change scores on the Short Form-36 Health Survey, and mean sleep interference scores.…”
Section: Pregabalinmentioning
confidence: 99%
“…Similar to gabapentin, pregabalin was developed as a treatment for epileptic seizures, but it has evolved to include other indications, such as neuropathic pain [50,51]. Their mechanisms of action require the binding to the high affinity α2-delta subunit protein of the voltagegated Ca 2+ channels [52], thereby reducing release of excitatory neurotransmitters in the central nervous system [53].…”
Section: Pregabalinmentioning
confidence: 99%